First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Drifting fish aggregation devices as a tool to study oceanic marine protected areas - Arthur Blanluet; Edward T. Game; Kydd Pollock; Nicholas H. Wolff; Jason D. Everett; Sandra Neubert; Daniel C. Dunn; Anthony J. Richardson (Fisheries Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Employing optical lightning data to identify lightning flashes associated to terrestrial gamma-ray flashes - Christoph Köhn; Matthias Heumesser; Olivier Chanrion; Victor Reglero; Nikolai Østgaard; H. J. Christian; T. J. Lang; R. J. Blakeslee; Torsten Neubert (Bulletin of Atmospheric Science and Technology, 2024)
Terrestrial gamma-ray flashes (TGFs) are bursts of energetic X- and gamma-rays emitted from thunderstorms. The Atmosphere-Space Interactions Monitor (ASIM) mounted onto the International Space Station (ISS) is dedicated to measure TGFs and optical signatures of lightning; ISS LIS (Lightning Imaging Sensor) detects lightning flashes allowing for simultaneous measurements with ASIM. Whilst ASIM measures $$\sim $$ ∼ 300-400 TGFs per year, ISS LIS detects $$\sim 10^6$$ ∼ 10 6 annual lightning flashes giving a disproportion of four orders of magnitude. Based on the temporal evolution of lightning flashes and the spatial pattern of the constituing events, we present an algorithm to reduce the number of space-detected flashes potentially associated with TGFs by $$\sim $$ ∼ 60% and of associated LIS groups by $$\sim $$ ∼ 95%. We use ASIM measurements to confirm that the resulting flashes are indeed those associated with TGFs detected at approx. 400 km altitude and thus benchmark our algorithm preserving 70–80% of TGFs from concurrent ASIM-LIS measurements. We compare how the radiance, footprint size and the global distribution of lightning flashes of the reduced set relates to the average of all measured lightning flashes and do not observe any significant difference. Finally, we present a parameter study of our algorithm and discuss which parameters can be tweaked to maximize the reduction efficiency whilst keeping flashes associated to TGFs. In the future, this algorithm will hence be capable of facilitating the search for TGFs in a reduced set of lightning flashes measured from space.

Development and Validation of a Western Blot Method to Quantify Mini-Dystrophin in Human Skeletal Muscle Biopsies - Catherine I. Soderstrom; Jennifer Larsen; Carolina Owen; David Gifondorwa; David Beidler; Florence H. Yong; Patricia Conrad; Hendrik Neubert; Steven A. Moore; Mohamed Hassanein (The AAPS Journal, 2022)
Duchenne muscular dystrophy (DMD) is a degenerative muscular disease affecting roughly one in 5000 males at birth. The disease is often caused by inherited X-linked recessive pathogenic variants in the dystrophin gene, but may also arise from de novo mutations. Disease-causing variants include nonsense, out of frame deletions or duplications that result in loss of dystrophin protein expression. There is currently no cure for DMD and the few treatment options available aim at slowing muscle degradation. New advances in gene therapy and understanding of dystrophin (DYS) expression in other muscular dystrophies have opened new opportunities for treatment. Therefore, reliable methods are needed to monitor dystrophin expression and assess the efficacy of new therapies for muscular dystrophies such as DMD and Becker muscular dystrophy (BMD). Here, we describe the validation of a novel Western blot (WB) method for the quantitation of mini-dystrophin protein in human skeletal muscle tissues that is easy to adopt in most laboratory settings. This WB method was assessed through precision, accuracy, selectivity, dilution linearity, stability, and repeatability. Based on mini-DYS standard performance, the assay has a dynamic range of 0.5–15 ng protein (per 5 µg total protein per lane), precision of 3.3 to 25.5%, and accuracy of − 7.5 to 3.3%. Our stability assessment showed that the protein is stable after 4 F/T cycles, up to 2 h at RT and after 7 months at − 70°C. Furthermore, our WB method was compared to the results from our recently published LC–MS method. Graphical Abstract Workflow for our quantitative WB method to determine mini-dystrophin levels in muscle tissues (created in Biorender.com). Step 1 involves protein extraction from skeletal muscle tissue lysates from control, DMD, or BMD biospecimen. Step 2 measures total protein concentrations. Step 3 involves running gel electrophoresis with wild-type dystrophin (wt-DYS) from muscle tissue extracts alongside mini-dystrophin STD curve and mini-DYS and protein normalization with housekeeping GAPDH.

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Drug Release from ß-Cyclodextrin Complexes and Drug Transfer into Model Membranes Studied by Affinity Capillary Electrophoresis - Kinda A. Darwish; Yahya Mrestani; Hans-Hermann Rüttinger; Reinhard H. H. Neubert (Pharmaceutical Research, 2016)

Seroprevalence of hepatitis E virus (HEV) in humans living in high pig density areas of Germany - Andi Krumbholz; Sebastian Joel; Paul Dremsek; Anne Neubert; Reimar Johne; Ralf Dürrwald; Mario Walther; Thomas H. Müller; Detlef Kühnel; Jeannette Lange; Peter Wutzler; Andreas Sauerbrei; et al. (Medical Microbiology and Immunology, 2014)

Prevalence of antibodies against hepatitis A virus among children and adolescents in Germany - A. Krumbholz; A. Neubert; H. Girschick; H. I. Huppertz; P. Kaiser; J. Liese; A. Streng; T. Niehues; J. Peters; A. Sauerbrey; H. Schroten; T. Tenenbaum; et al. (Medical Microbiology and Immunology, 2013)

Lecithin-Based Microemulsions for Targeted Delivery of Ceramide AP into the Stratum Corneum: Formulation, Characterizations, and In Vitro Release and Penetration Studies - Fitsum F. Sahle; Hendrik Metz; Johannes Wohlrab; Reinhard H. H. Neubert (Pharmaceutical Research, 2013)

A Novel Approach for In Vitro Studies Applying Electrical Fields to Cell Cultures by Transformer-Like Coupling - R. Hess; H. Neubert; A. Seifert; S. Bierbaum; D. A. Hart; D. Scharnweber (Cell Biochemistry and Biophysics, 2012)

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Analysis of vaccine-virus-associated rabies cases in red foxes (Vulpes vulpes) after oral rabies vaccination campaigns in Germany and Austria - Thomas Müller; H.-J. Bätza; A. Beckert; C. Bunzenthal; J. H. Cox; C. M. Freuling; A. R. Fooks; J. Frost; L. Geue; A. Hoeflechner; D. Marston; A. Neubert; et al. (Archives of Virology, 2009)

Women encounter ADRs more often than do men - Y. Zopf; C. Rabe; A. Neubert; K. G. Gaßmann; W. Rascher; E. G. Hahn; K. Brune; H. Dormann (European Journal of Clinical Pharmacology, 2008)

Penetration Profile of Taurine in the Human Skin and Its Distribution in Skin Layers - D. L. P. da Silva; S. B. Thiago; F. A. Pessôa; Y. Mrestani; H. H. Rüttinger; J. Wohlrab; R. H. H. Neubert (Pharmaceutical Research, 2008)

Arrangement of ceramide [EOS] in a stratum corneum lipid model matrix: new aspects revealed by neutron diffraction studies - Doreen Kessner; Mikhail Kiselev; Silvia Dante; Thomas Hauß; Peter Lersch; Siegfried Wartewig; Reinhard H. H. Neubert (European Biophysics Journal, 2008)

Localisation of partially deuterated cholesterol in quaternary SC lipid model membranes: a neutron diffraction study - Doreen Kessner; Mikhail A. Kiselev; Thomas Hauß; Silvia Dante; Siegfried Wartewig; Reinhard H. H. Neubert (European Biophysics Journal, 2008)

Fatty acid interdigitation in stratum corneum model membranes: a neutron diffraction study - A. Ruettinger; M. A. Kiselev; Th. Hauss; S. Dante; A. M. Balagurov; R. H. H. Neubert (European Biophysics Journal, 2008)

What can we learn about the lipid vesicle structure from the small-angle neutron scattering experiment? - M. A. Kiselev; E. V. Zemlyanaya; V. K. Aswal; R. H. H. Neubert (European Biophysics Journal, 2006)

Substrate Specificity and Mechanism of the Intestinal Clonidine Uptake by Caco-2 Cells - Wiebke Fischer; Linda Metzner; Kathrin Hoffmann; Reinhard H. H. Neubert; Matthias Brandsch (Pharmaceutical Research, 2006)

New insights into the structure and hydration of a stratum corneum lipid model membrane by neutron diffraction - M. A. Kiselev; N. Y. Ryabova; A. M. Balagurov; S. Dante; T. Hauss; J. Zbytovska; S. Wartewig; R. H. H. Neubert (European Biophysics Journal, 2005)

Characterization of Mixtures of Alkyl Polyglycosides (Plantacare) by Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry - Andrea V. Khn; Reinhard H. H. Neubert (Pharmaceutical Research, 2004)

Role of Ascorbic Acid in Stratum Corneum Lipid Models Exposed to UV Irradiation - Hagen Trommer; Rolf Böttcher; Andreas Pöppl; Joachim Hoentsch; Siegfried Wartewig; Reinhard H. H. Neubert (Pharmaceutical Research, 2002)

Investigation of Pharmaceutical Oil/Water Microemulsions by Small-Angle Scattering - Anuj Shukla; Martin Janich; Konstanze Jahn; Annett Krause; Mikael A. Kiselev; Reinhard H. H. Neubert (Pharmaceutical Research, 2002)

Characterization of Povidone Products by Means of 13C-NMR, MALDI-TOF, and Electrospray Mass Spectrometry - Klaus Raith; Andrea V. Kühn; Fred Rosche; Raik Wolf; Reinhard H. H. Neubert (Pharmaceutical Research, 2002)

Penetration Studies of Clotrimazole from Semisolid Formulation Using Step-Scan FT-IR Photoacoustic Spectroscopy - Anja Schendzielorz; Bui Duc Hanh; Reinhard H. H. Neubert; Siegfried Wartewig (Pharmaceutical Research, 1999)

Mixing Ratios and Photostationary State of NO and NO2 Observed During the POPCORN Field Campaign at a Rural Site in Germany - F. Rohrer; D. Brüning; E. S. Grobler; M. Weber; D. H. Ehhalt; R. Neubert; W. Schüßler; I. Levin (Journal of Atmospheric Chemistry, 1998)

Partition Behaviour of Drugs in Microemulsions Measured by Electrokinetic Chromatography - Y. Mrestani; R. H. H. Neubert; A. Krause (Pharmaceutical Research, 1998)

Ofloxacin in juvenile non-human primates and rats. Arthropathia and drug plasma concentrations - R. Stahlmann; H. J. Merker; N. Hinz; I. Chahoud; J. Webb; W. Heger; D. Neubert (Archives of Toxicology, 1990)

Influence of 13-cis and all- trans retinoic acid on rat embryonic development in vitro: correlation with isomerisation and drug transfer to the embryo - S. Klug; J. Creech Kraft; E. Wildi; H. -J. Merker; T. V. N. Persaud; H. Nau; D. Neubert (Archives of Toxicology, 1989)